Blood-Based Markers of Neuronal Injury in Adult-Onset Myotonic Dystrophy Type 1 - van der Plas, Ellen; Long, Jeffrey D.; Koscik, Timothy R.; Magnotta, Vincent; Monckton, Darren G.; Cumming, Sarah A.; Gottschalk, Amy C.; Hefti, Marco; Gutmann, Laurie; Nopoulos, Peggy C. (Frontiers in Neurology, 2022)
Introduction: The present study had four aims. First, neuronal injury were compared between individuals with and without adult-onset myotonic dystrophy type 1 (DM1), including neurofilament light (NF-L), total tau, glial fibrillary acidic protein (GFAP) and ubiquitin C-terminal hydrolase (UCH-L1). Second, the impact of age and CTG repeat on brain injury markers was evaluated. Third, change in brain injury markers across the study period was quantified. Fourth, associations between brain injury markers and cerebral white matter (WM) fractional anisotropy (FA) were identified. Methods: Yearly assessments, encompassing blood draws and diffusion tensor imaging on a 3T scanner, were conducted on three occasions. Neuronal injury markers were quantified using single molecule array (Simoa). Results: The sample included 53 patients and 70 controls. NF-L was higher in DM1 patients than controls, with individuals in the premanifest phases of DM1 (PreDM1) exhibiting intermediate levels (χ2(2)=38.142, P<0.001). Total tau was lower in DM1 patients than controls (Estimate=-0.62, 95% confidence interval [CI] -0.95:-0.28, P<0.001), while GFAP was elevated in PreDM1 only (Estimate=30.37, 95% CI 10.56:50.19, P=0.003). The age by CTG interaction predicted NF-L: patients with higher ePAL had higher NF-L at a younger age, relative to patients with lower CTG repeat; however, the latter exhibited faster age-related change (Estimate=-0.0021, 95% CI -0.0042:-0.0001, P=0.045). None of the markers changed substantially over the study period. Finally, cerebral WM FA predicted NF-L (Estimate=-42.86, 95% CI -82.70:-3.02, P=0.035). Interpretation: While NF-L appears sensitive to disease onset and severity, its utility as a marker of progression remains to be determined. The tau assay may have low sensitivity to tau pathology associated with DM1.